Aerophoto interpretation of geological structures on the surface above the Predjama cave - Šebela, Stanka (Acta carsologica, 1995)
Stereoscopic observing of aerophoto images on the scale 1:5000 is very good information to determine preliminary geologic structural elements in the field. Characteristic morfological structures like dolines, and series of dolines show positions of tectonic crushed zones. Also a lithological difference such as the border between limestone and flysh is visible as a characteristic morphologic step. The nappe border between Triassic dolomite and Cretaceous limestone is determined also. This method is best confirmed with detailed tectonic-lithological mapping in the field on the scale 1:5000. The case of Predjama shows some differences in comparing both methods.
Keywords: aerofotogrametrija; aerosnemanje; geologija; geology; kras (geologija); Predjama